Influence of tobacco smoke on carcinogenic PAH composition in indoor PM10 and PM2.5 - K. Slezakova (2009)
Because of the mutagenic and/or carcinogenic properties, Polycyclic Aromatic Hydrocarbons (PAH), have a direct impact on human population. Consequently, there is a widespread interest in analysing and evaluating the exposure to PAH in different indoor environments, influenced by different emission sources. The information on indoor PAH is still limited, mainly in terms of PAH distribution in indoor particles of different sizes: thus, this study evaluated the influence of tobacco smoke on PM10 and PM2.5 characteristics. namely on their PAH compositions, with further aim to understand the negative impact of tobacco smoke on human health. Samples were collected at one site influenced by tobacco smoke and at one reference (non-smoking) site using low-volume samplers; the analyses of 17 PAH were performed by Microwave Assisted Extraction combined with Liquid Chromatography (MAE-LC). At the site influenced by tobacco smoke PM concentrations were higher 650% for PM10, and 720% for PM2.5. When influenced by smoking, 4 ring PAH (fluoranthene, pyrene, and chrysene) were the most abundant PAH, with concentrations 4600-21 000% and 5100-20 800% higher than at the reference site for PM10 and PM2.5, respectively, accounting for 49% of total PAH (Sigma(PAH)). Higher molecular weight PAH (5-6 rings) reached concentrations 300-1300% and 140-1700% higher for PM10 and PM2.5, respectively, at the site influenced by tobacco smoke. Considering 9 carcinogenic PAH this increase was 780% and 760% in PM10 and PM2.5, respectively, indicating the strong potential risk for human health. As different composition profiles of PAH in indoor PM were obtained for reference and smoking sites, those 9 carcinogens represented at the reference site 84% and 86% of Sigma(PAH) in PM10 and PM2.5, respectively, and at the smoking site 56% and 55% of Sigma(PAH) in PM10 and PM2.5, respectively. All PAH (including the carcinogenic ones) were mainly present in fine particles, which corresponds to a strong risk for cardiopulmonary disease and lung cancer; thus, these conclusions are relevant for the development of strategies to protect public health.